2021
DOI: 10.1002/ehf2.13417
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac reverse remodelling and health status in patients with chronic heart failure

Abstract: AimsThis study aims to assess long-term changes in left ventricular ejection fraction (LVEF) together with echocardiographic markers of cardiac remodelling and their association with prognosis and patient-reported quality of life (QoL). Methods and resultsWe conducted a retrospective analysis of serial echocardiograms performed between January 2009 and December 2019 in 1089 patients (median age 63 years, 71.0% men) enrolled in the Mazankowski Heart Function Clinic Registry who had at least two echocardiograms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
(90 reference statements)
0
12
0
Order By: Relevance
“…In addition to the effect on mortality and hospitalization outcomes, Peter Wohlfahrt et al confirmed that HFrecEF significantly improved the quality of life in patients with heart failure ( 9 ). However, the prognostic effect of recovered ejection fraction was inconsistent or even non-significant ( 10 , 12 , 16 ). After a systematic review of all relevant reports, we have pooled the quantified impact of HFrecEF on prognosis, which provided explicit evidence that HFrecEF, recently redefined as HFimpEF, is a novel entity in patients with heart failure needing more attention and evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the effect on mortality and hospitalization outcomes, Peter Wohlfahrt et al confirmed that HFrecEF significantly improved the quality of life in patients with heart failure ( 9 ). However, the prognostic effect of recovered ejection fraction was inconsistent or even non-significant ( 10 , 12 , 16 ). After a systematic review of all relevant reports, we have pooled the quantified impact of HFrecEF on prognosis, which provided explicit evidence that HFrecEF, recently redefined as HFimpEF, is a novel entity in patients with heart failure needing more attention and evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Reverse left ventricular remodeling with a more favorable neurohormonal profile is probably the main mechanism of HFimpEF or HFrecEF, which was characterized as the reduction of left ventricular end-diastolic and end-systolic volume, left ventricular mass index, and E/e′ ratio ( 5 , 16 ). Kramer et al had reported that reverse left ventricular remodeling is associated with fewer heart failure hospitalizations and reduced cardiovascular mortality, and the degree of reverse left ventricular remodeling is directly related to improved cardiac survival ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our second study aim represented a novelty, to our knowledge, and it is probably the most important finding of our results. Previous studies have shown that patients with HFimpEF or ‘recovered’ LVEF had a better prognosis 15–23 ; but that was not the objective of the present study. Moreover, QoL was previously associated with outcomes in patients with HF 25–30 .…”
Section: Discussionmentioning
confidence: 86%
“…The 2021 universal definition of HF specifically describes the criteria for patients with HF that have shown improved LVEF (HFimpEF) as follows: HF with a baseline LVEF ≤40%, a ≥10‐point increase from baseline LVEF, and a second measurement of LVEF >40% 14 . Improvement or recovery in LVEF has been associated with better clinical outcomes, including HF‐related hospitalizations and survival 15–23 . However, the influence of LVEF improvement (or LVEF recovery) on QoL, although reported in a small number of studies, 6,22–24 has not been completely established.…”
Section: Introductionmentioning
confidence: 99%
“…5,30 We also conducted a risk analysis to assess the association between LVEF trajectory and MACE. The utility of serial LVEF evaluation for MACE has been previously demonstrated in traditional HF, 31,32 but never before in MD. We determined that patients with a reduction in LVEF on follow-up TTE were at greater risk of MACE than patients with preserved LVEF, while dimensional changes lacked independent prognostic value.…”
Section: Clinical Variables Hr (95% Ci) P-value Hr (95% Ci) P-valuementioning
confidence: 99%